Phase 1 clinical trials of DAS181, an inhaled sialidase, in healthy adults - Zenilman, Jonathan M.; Fuchs, Edward J.; Hendrix, Craig W.; Radebaugh, Christine; Jurao, Robert; Nayak, Seema U.; Hamilton, Robert G.; McLeod Griffiss, J. (Antiviral research, 2015)
•DAS181 is a sialidase with activity against influenza and parainfluenza.•Daily inhalation of 20mg/day was well tolerated for up to seven days.•Daily inhalation of 20mg/day for >7days was associated with respiratory toxicity.•Longer dose schedules were associated with immunogenicity. DAS181, (study drug, Fludase®) was developed for treatment of influenza and parainfluenza infections. Delivered by inhalation, DAS181 cleaves sialic acid receptors from respiratory epithelial cells. Treatment of influenza for three days with DAS181 reduced viral shedding. To increase deposition in the upper airways and decrease systemic absorption, the particle size was increased to 10μm. We conducted two Phase I trials with three cohorts, randomized 2:1, active drug to placebo. The initial cohort got a single 20mg dose of DAS181, or placebo; the second, 20mg DAS181 or placebo for 10days, and the third got 20mg of DAS181 or placebo for 3days. Formulations differed slightly in their excipients. Subjects in the 1- and 3-day cohorts completed dosing without serious adverse events. Two subjects in the 10-day cohort stopped at Day 9 after developing respiratory and systemic symptoms, and a third experienced a decrease in FEV1 (Forced Expiratory Volume in 1s) after the 9th dose and a further decline after the 10th dose. Plasma DAS181, in the 10-day cohort, peaked and began falling before the last dose. Antibodies, predominately IgG with neutralizing activity, were detected in 15/18 subjects by Day 30. The highest IgG concentrations were in the 10-day cohort. The respiratory adverse events occurring after seven days and rapid drug clearance during continued dosing are consistent with the induction of DAS181 antibodies. This could preclude use of this medication for longer than seven days or for repeated courses. (These studies have been registered at ClinicalTrials.gov under registration Nos. NCT 00527865 and NCT 01651494.)